Climate Change Challenges on Fisheries and Aquaculture - Dereje Tewabe (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2014)
Climate change poses new challenges to the sustainability of fisheries and aquaculture systems, with serious implications for the 520 million people who depend on them for their livelihoods and then early 3 billion people for whom fish is an important source of animal protein [1]. Two-thirds of all reefs are in developing countries, and 500 million people in the tropics depend heavily on reefs for food, livelihoods, protection from natural disasters and other basic needs. For many coastal communities in reef areas, fishing activities are the sole source of income. Climate changes may affect fisheries and aquaculture directly by influencing fish stocks and the global supply of fish for consumption, or indirectly by influencing fish prices or the cost of goods and services required by fishers and fish farmers. Potential loss of species or shift in composition for capture fisheries and impacts on seed availability for aquaculture, changes in precipitation and water availability are major impacts of climate change. Climate change lowers water quality causing more disease and increased competition with other water users which altered and reduced freshwater supplies with greater risk of drought. Fishing communities that depend on inland fisheries resources are likely to be particularly vulnerable to climate change. Higher inland water temperatures may reduce the availability of wild fish stocks by harming water quality, worsening dry season mortality, bringing new predators and pathogens, and changing the abundance of food available to fishery species.